Fungsi dan Kewenangan Peradilan Tata Negara dalam Sistem Ketatanegaraan Indonesia - Natalia Beka; Oksix Tari; Nadya Paa; Selfi Kase; Rosalinda Tulit; Nindy Nenobais; Yunike Lely; Fadil Mas’ud (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The constitutional judiciary occupies a strategic position in Indonesia’s constitutional system because it serves to uphold the supremacy of the Constitution while protecting the constitutional rights of citizens. This article examines the status, functions and division of powers of the Constitutional Court and the Supreme Court as the two main pillars of Indonesia’s constitutional judiciary following the amendments to the 1945 Constitution. The research employs a normative legal method using a statutory approach and a conceptual approach, through the examination of primary and secondary legal sources analyzed using descriptive-qualitative methods. The results of the study indicate that the constitutional judiciary performs three main functions: protecting citizens’ constitutional rights, reviewing the constitutionality of legislative acts and resolving jurisdictional disputes among state institutions. This study also found that the division of authority between the Constitutional Court and the Supreme Court which is coordinative rather than hierarchical has the potential to create a dualism in the review of legal norms that requires further harmonization, while the growing phenomenon of “no viral, no justice” reveals a new sociological dimension that also influences the legitimacy of administrative court rulings in the digital age.